Complications and pregnancy outcome in women with preeclampsia and eclampsia - Thiripurasundari, G.; Christe, D. M.; Shobha, S.; Sangeetha, V.; Sevugaperumal, Suganya (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: One of the complications of pregnancy which till today challenges the obstetrician is preeclampsia and its severe form of eclampsia. Objective of this study was to find out the complications and outcome of pregnant women with preeclampsia and eclampsia admitted in a tertiary referral center. Methods: Case records, in labor room, were scrutinized to find out the number and the outcome of pregnancy, in women admitted with preeclampsia or eclampsia in the year 2018. Results: Pregnant women admitted with preeclampsia or eclampsia numbered 2511 and, 109 women developed complications. Maternal complications, were more often seen in mothers, (62.4%) of female babies. Only 37.6% of mothers of male babies developed complications. Complications seen were Renal complications in 34.8%, Hematological complications in 33%, Neurological complications in 25.6%, Pulmonary complications in 16.5%, ophthalmological complications in 11% and Sepsis in 6.4% and MODS in 10%. Of total maternal deaths, 34% was caused by complications of preeclampsia or eclampsia. Major cause of maternal death was MODS and Pulmonary complications. Nearly, 62.3% of babies born had birth weight of 1.8 kg and nearly one-third of babies (26.6%) were dead born. Conclusions: The incidence of preeclampsia and eclampsia in our referral center for the year 2018 was 15%, and 4.3% of women developed complications, and 6% died, making preeclampsia and eclampsia the causative factor for 34% of total maternal deaths. Major maternal complications were Renal, Hematological, Neurological, Pulmonary and MODS. Complications of preeclampsia were more often present in 62.4% mothers of female babies in contrast to 37.6% of mothers of male babies. Nearly one-third of babies (26.6%) were dead born.